2013
DOI: 10.2169/internalmedicine.52.8531
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System Lymphoma Initially Diagnosed as Tumefactive Multiple Sclerosis after Brain Biopsy

Abstract: A 72-year-old man was admitted with left homonymous hemianopsia and hemiparesis. Magnetic resonance imaging revealed a heterogeneously enhanced lesion in the right parietal lobe. A brain biopsy showed acute demyelination without malignancy, which led to a diagnosis of tumefactive multiple sclerosis (MS). The patient received corticosteroid therapy and experienced clinical and radiological improvement. Six months later, new lesions appeared, and a second biopsy revealed proliferation of dysplastic lymphocytes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 14 publications
1
16
0
1
Order By: Relevance
“…Demyelinating lesions are called "sentinel lesions" and are associated with contrast enhancement on MRI (3). Similar cases of the development of "sentinel lesions" preceding primary CNS lymphoma have been reported (4,5).…”
Section: Discussionsupporting
confidence: 72%
“…Demyelinating lesions are called "sentinel lesions" and are associated with contrast enhancement on MRI (3). Similar cases of the development of "sentinel lesions" preceding primary CNS lymphoma have been reported (4,5).…”
Section: Discussionsupporting
confidence: 72%
“…In addition, Ohe et al . reported a case of PCNSL that was initially diagnosed as tumefactive multiple sclerosis after brain biopsy . This case demonstrated that PCNSL can mimic multiple sclerosis both clinically and radiologically.…”
Section: Discussionmentioning
confidence: 84%
“…Ohe et al . described a case of primary CNS lymphoma that was initially diagnosed as tumefactive multiple sclerosis after brain biopsy, and demonstrated that primary CNS lymphomas can resemble demyelinating disease both clinically and radiologically . Sharma et al .…”
Section: Primary Cns Lymphomas and Demyelinating Diseasesmentioning
confidence: 99%
“…Ohe et al described a case of primary CNS lymphoma that was initially diagnosed as tumefactive multiple sclerosis after brain biopsy, and demonstrated that primary CNS lymphomas can resemble demyelinating disease both clinically and radiologically. 39 Sharma et al reported that primary CNS lymphomas have an accompanying component of demyelination that may increase following corticosteroid-induced tumor regression. 40 In addition, several cases of spontaneous regression of primary CNS lymphomas without steroid administration have been reported.…”
Section: Primary Cns Lymphomas and Demyelinating Diseasesmentioning
confidence: 99%